Perceptions of psychological well-being in UK law academics. Issue 3 (3rd July 2018) - Wilson, J. Clare; Strevens, Caroline
ABSTRACT: This study provides evidence that changing and increasing expectations of university, of students, and of academics of themselves have had an impact upon the perceptions of well-being in the law teachers who responded to this survey. A total of 185 UK law teachers completed a large survey which included demographic questions (age, academic qualifications, and experience), four questionnaires and a series of open-ended questions. Although most reported depression, anxiety and stress levels within the normal range, those who reported high stress levels were significantly more likely to report lower hope scores and higher obstruction of values scores as well as significantly less environmental mastery and self-acceptance. The results reported here indicate the importance of autonomy to law teachers. It is suggested that this is an issue that requires further investigation because of the potential for levels of psychological distress to increase.